International students experiencing super-mobility in Scotland, Malta, Sweden, and Portugal through the TourDC programme - Michel dit Ferrer, Alice (2022)
This dissertation aims to explore and complete the existent literature regarding student mobility in Europe. Furthermore, it intends to provide an understanding of the motivations, perceptions, and pre-conceptions of Erasmus Mundus students, also known as `super mobile` students. This dissertation will focus on students undertaking the EMJMD in Tourism and Culture (TourDC), taking place in Scotland, Malta, Sweden, and Portugal. The research has been made through semi-structured interviews conducted amongst a sample of fourteen TourDC students or alumni X. It thus attempts to further our understanding about how students live their academic and cultural experiences during the Erasmus Mundus TourDC programme. The obligation of the findings are firstly understanding the motivations of Erasmus Mundus TourDC students; secondly, the study of the cultural acclimatisation to the countries visited during the programme; and finally the identification of potential patterns for Erasmus Mundus students in terms of family, education, and cultural backgrounds. This paper demonstrates that almost all the students had a positive experience throughout their mobilities and therefore now feel prepared to pursue their chosen career path after graduation.